2008
DOI: 10.1007/bf03326014
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management in the electronic industry

Abstract: Green supply chain management has emerged as a proactive approach for improving environmental performance of processes and products in accordance with the requirements of environmental regulations. Various approaches for implementing green supply chain management practices has been proposed and recognized in previous literatures, yet no investigation has identified the reliability and validity of such approaches particularly in electronic industry. This study examines the consistency approaches by factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(130 citation statements)
references
References 27 publications
0
128
0
2
Order By: Relevance
“…In order to solve these pollution problems, environmental management (EM) and green supply chain management (GSCM) have been widely adopted by enterprises with the aim of reducing pollution and evaluating environmental performance (Boiral, 2002;Chien and Shih, 2007;Hsu and Hu, 2008). Environmental protection and performance have become two of the world's most important priorities in order to attain sustainable development (Nouri et al, 2008) Over the previous decade, EM has moved away from a regulatory-based approach to one focusing on continuous development.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these pollution problems, environmental management (EM) and green supply chain management (GSCM) have been widely adopted by enterprises with the aim of reducing pollution and evaluating environmental performance (Boiral, 2002;Chien and Shih, 2007;Hsu and Hu, 2008). Environmental protection and performance have become two of the world's most important priorities in order to attain sustainable development (Nouri et al, 2008) Over the previous decade, EM has moved away from a regulatory-based approach to one focusing on continuous development.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al verified the inter-relationship among continuous improvement, supplier management, environmental management, and manufacturing competitiveness in both China and Taiwan electrical/electronic companies [46]. Hsu and Hu suggested that companies could emphasize suppliers' management performance when implementing GSCM through a survey of Taiwan electronic companies [23]. Because Taiwan is a key player in the global electronics industry, this study aims to determine the major factors affecting environmental performance in the Taiwanese computer industry in order to provide empirical results as a general reference for GCSM.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Tian et al developed a system dynamics model to promote the diffusion of GCSM in China's automobile industry [22]. Hsu and Hu examined consistency approaches by fuzzy Analytic Hierarchy Process (AHP) to determine the adoption and implementation of GSCM in Taiwanese electronic industry [23]. GSCM is gaining increasing interest among researchers and practitioners of operations and supply chain management [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Spiegler et al (2012) illustrated the adaptability of SC during the arrangement of unpredictable events, responding to disruptions, and sustaining progress operations. Hsu and Hu (2008) demonstrated that green SCM is a proactive approach developed during the improvement of the environmental performance of operations following end products within a suitable requirement of an environmental regulation. Zhu et al (2010) indicated that green SCM is an environmental innovation.…”
Section: Resilient Scmmentioning
confidence: 99%